Cyclosporine in the Management of Impetigo Herpetiformis: A Case Report and Review of the Literature - Aikaterini Patsatsi; Theodoros D. Theodoridis; Dimitrios Vavilis; Vasilios Tzevelekis; Aikaterini Kyriakou; Dimitrios Kalabalikis; Dimitrios Sotiriadis (Karger Publishers, 2013)
A 27-year-old female, gravida 1, para 0, in week 22 of pregnancy, presented with an eruption consisting of annular erythematosquamous plaques with an active polycyclic elevated border comprised of superficial micropustules. Clinical and histological features were typical of impetigo herpetiformis (IH). Systemic steroids resulted in an unstable condition, with no resolution of lesions. Resistance to the above therapeutic scheme served as a stimulus to discuss the use of cyclosporine as a therapeutic option in this condition. Reviewing the limited literature, cyclosporine seems to serve not as a monotherapy in the management of IH but as an additional medication, in order to achieve a stable course of the disease and avoid high doses of systemic steroids.